Clinical cases of measles in pregnant women - O. V. Riabokon; N. H. Izbytska; S. O. Bilokobyla; T. Ye. Onishchenko; Yu. Yu. Riabokon (Zaporozhye State Medical University, 2020)
The aim of the work is to analyze the clinical course of measles in hospitalized pregnant women for the period of 2017-2019 years. Materials and methods. The clinical course of measles was analyzed in 4 pregnant patients with this disease aged from 19 to 30 years, who were hospitalized in the Regional Infectious Clinical Hospital during 2017-2019 years. The diagnosis of measles was established according to the WHO criteria (2013). All pregnant women with measles had epidemiological history of contact with measles patients and in all cases diagnosis of measles was confirmed by detection measles IgM in the Zaporizhzhia Regional Laboratory Center of the Ministry of Health of Ukraine. Results. It was found that in all pregnant women who were included in the study, measles developed in the third trimester of pregnancy, one patient was pregnant with twins. The development of measles was accompanied by the appearance of typical clinical symptoms with formation of moderate (n = 2) and severe (n = 2) course. One pregnant woman had never been vaccinated against measles during her lifetime; other three patients had no documented evidence of previous measles vaccination. Most of the pregnant women (3 out of 4) had complications of measles from respiratory system: acute bronchitis (n = 1), acute bronchitis with pulmonary edema and respiratory failure of I-II degree (n = 1), community-acquired lower lobe right-sided pneumonia, left lung atelectasis, respiratory failure of III degree (n = 1). Only in one 26-year-old pregnant measles had moderate course without complications. In two pregnant women development of complications needed treatment in the intensive care unit. In 30-year-old pregnant woman with twins with gestational age of 27-28 weeks from the first day of the rash, complications like measles enteritis appeared, and from the second day of the rash there were signs of acute respiratory failure due to development of pulmonary edema. On the background of complex medical treatment with use of oxygen therapy, patient recovered, pregnancy progressed without complications. However, in one unvaccinated 25-year-old woman, who had not been vaccinated with measles, severe course of the disease was accompanied not only by the development of complications, but also had adverse effects on pregnancy. In this patient, measles was complicated by community-acquired right-sided pneumonia of group IV, left lung atelectasis, acute respiratory failure degree III, toxic-hypoxic encephalopathy and brain edema, which required mechanical ventilation. In addition, chronic hepatitis C was first diagnosed. Against this background, there was premature birth within 30 weeks. Conclusions. According to analysis of four observations we can determine that measles in pregnancy has both moderate and severe course, but development of complications from respiratory system was recorded in the majority of patients (3 out of 4 patients). In severe cases of measles in pregnant women treatment in the intensive care unit was required due to development of pulmonary edema on the background of acute bronchitis in combination with measles enteritis (n = 1), community-acquired right-sided pneumonia in combination with left lung atelectasis (n = 1). The above clinical observation demonstrates the development of a very severe complicated course of measles in previously unvaccinated 25-year-old pregnant, which led to premature birth in the gestation period of 30 weeks.